Contribution of agriculture sector to national economy in Nepal - Adhikari, Santosh (Journal of Agriculture and Environment, 2015)
Agriculture is the mainstay of majority of Nepalese people which provides employment, foods and shelter. However, the investment in agriculture in not encouraging, received only about 3 percent of total government outlays during 2002 to 2014. In the study, Gross Domestic Product was regressed with Domestic Savings, Government Expenditure on Agriculture and Foreign Direct Investment on Agriculture with the data from FY 2002/03 to 2014/15. Regression reveals the degree of association among these variables is significant at 5 % level of significance (R=0.991, P=0.005<0.05). The analysis showed that the contribution of Government Expenditure on Agriculture to Gross Domestic Product was found significant whereas the Domestic Savings and Foreign Direct Investment on Agriculture were found insignificant. The compound annual growth rate of Government’s expenditure was found slightly lower than that of budget allocated to Ministry of Agricultural Development. In sum, the study concluded that the Government Expenditure on Agriculture is crucial for the national economy.